COVID-19 vaccine-induced autoimmune hyperthyroidism: Graves’ disease - Murugan, Avaniyapuram Kannan; Alzahrani, Ali S. (Frontiers in Immunology, 2025)
Graves’ disease (GD) is an autoimmune disorder that results in hyperthyroidism, in which the immune system mistakenly targets the thyroid gland, causing it to produce excessive amounts of thyroid hormones. Genetic predisposition, environmental factors such as infections and stress, disruptions in the gut microbiome, excessive iodine intake, and epigenetic changes have all been implicated in the development of GD. The recent pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) posed a serious global health crisis. The emergence of COVID-19 vaccines has been pivotal in combating the viral infection and its spread. However, reports of rare adverse events, including the development of autoimmune disorders such as GD following vaccination, have raised concerns. Autoimmune factors play a critical role in the pathogenesis of GD, particularly through the production of autoantibodies targeting the thyroid gland. In this review, reported cases are critically analyzed to elucidate commonalities and potential triggers for the development of this autoimmune disorder, highlighting the vital role of autoimmune mechanisms in inducing GD. We also discuss the molecular mechanisms underlying vaccine-induced autoimmunity, including antigen presentation, bystander activation, molecular mimicry, and the induction of inflammatory factors following vaccination. Understanding these mechanisms in COVID-19 vaccine-induced GD could enhance patient care and guide vaccination policies.